2015
DOI: 10.1152/ajpregu.00323.2014
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fatty acids and acidic pH upregulate UT-B, GPR41, and GPR4 in rumen epithelial cells of goats

Abstract: Currently, the mechanism(s) responsible for the regulation of urea transporter B (UT-B) expression levels in the epithelium of the rumen remain unclear. We hypothesized that rumen fermentation products affect ruminal UT-B expression. Therefore, the effects of short-chain fatty acids (SCFA), pH, ammonia, and urea on mRNA and protein levels of UT-B were assayed in primary rumen epithelial cell cultures and in rumen epithelium obtained from intact goats. In vitro, SCFA and acidic pH were found to synergetically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 65 publications
3
39
4
Order By: Relevance
“…concentration specifically regulate urea transport (Lu et al 2014). Most recently, studies in goat rumen have confirmed that SCFAs and pH are the key factors in dietary regulation of UT-B expression (Lu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…concentration specifically regulate urea transport (Lu et al 2014). Most recently, studies in goat rumen have confirmed that SCFAs and pH are the key factors in dietary regulation of UT-B expression (Lu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sheep rumen expresses both UT-B1 and UT-B2 transcripts by PCR, and urea transport was regulated by changes in pH and ammonia concentrations (50). In primary cultures of goat rumen epithelial cells, short-chain fatty acids and acid pH increased UT-B mRNA and protein abundance (51). Ruminal UT-B protein was also increased when the goats were fed a diet with large amounts of nitrogen and non-fiber carbohydrates (51).…”
Section: Ut-bmentioning
confidence: 99%
“…In primary cultures of goat rumen epithelial cells, short-chain fatty acids and acid pH increased UT-B mRNA and protein abundance (51). Ruminal UT-B protein was also increased when the goats were fed a diet with large amounts of nitrogen and non-fiber carbohydrates (51). …”
Section: Ut-bmentioning
confidence: 99%
“…Our previous studies have shown that dietary concentrate promotes microbial fermentation and energetic absorption in the goat rumen (Lu et al, 2015;Yan, Zhang, & Shen, 2014). In the present study, we first investigated the compositional recovery of rumen fluid and mucosal microbiota in goats undergoing a 10-day streptomycin (ST) treatment.…”
Section: Introductionmentioning
confidence: 99%